2022
DOI: 10.1097/yco.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Brain vasculature disturbance in schizophrenia

Abstract: Purpose of reviewThe vascular hypothesis of schizophrenia (SZ) postulates that brain endothelial dysfunction contributes to brain pathophysiology. This review discusses recent evidence for and against this hypothesis, including data related to blood–brain barrier (BBB), brain endothelium, and brain blood supply, to provide a critical weighed update.Recent findingsDifferent studies report a consistent proportion of SZ patients showing increased BBB permeability, reflected by higher levels of albumin in the cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 141 publications
(226 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, for many of the pathways analyzed, except for the WNT and mTOR pathways which seem to be consistently downregulated in SZ, different studies show variations with respect to the direction of this dysregulation regarding gene or protein expression. This may be a reflection of the high genetic heterogeneity present in SZ, especially in genes described as highly variable for this disease, rather than through gene expression or variant number ( Huang et al, 2020 ; Puvogel et al, 2022 ). Taking into consideration the variability in gene expression in SZ reviewed in this and other articles, we propose the existence of molecular patterns that may be related to specific symptoms, severity, and even responses to medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, for many of the pathways analyzed, except for the WNT and mTOR pathways which seem to be consistently downregulated in SZ, different studies show variations with respect to the direction of this dysregulation regarding gene or protein expression. This may be a reflection of the high genetic heterogeneity present in SZ, especially in genes described as highly variable for this disease, rather than through gene expression or variant number ( Huang et al, 2020 ; Puvogel et al, 2022 ). Taking into consideration the variability in gene expression in SZ reviewed in this and other articles, we propose the existence of molecular patterns that may be related to specific symptoms, severity, and even responses to medication.…”
Section: Discussionmentioning
confidence: 99%
“…As in most neurological disorders, the main descriptions of SZ physiopathology have been focused on neuronal deficiencies. Altered cerebral connectivity and brain dynamics, abnormalities in the excitatory/inhibitory balance, as well as failure to specify specific neuron identities have been described ( Spencer, 2009 ; Kantrowitz and Javitt, 2010 ; Inan et al, 2013 ; Puvogel et al, 2022 ). In addition to these neuronal alterations, increasing evidence has linked SZ to vascular impairments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years several studies identified BBB dysfunction and its increased permeability as potentially important factor in the development of psychiatric disorders [4,13,14].…”
Section: The Structure Of the Bbbmentioning
confidence: 99%
“…The roles of neurotransmission disturbances, immune response, and low-grade inflammation ("low-grade encephalitis") have been all implied [18,19]. Recent data indicate that the oxidative stress associated with neuroinflammation and neurovascular endotheliopathy can lead to impairment of BBB integrity and decreased cerebral perfusion and disruption of neuronal homeostasis in patients with schizophrenia [13,19]. The damage to occluding compounds between endothelial cells of continuous BBB capillaries (i.e., decreased CLDN5 expression in the hippocampus) has been demonstrated in schizophrenia [20].…”
Section: Bbb and Schizophreniamentioning
confidence: 99%